TikTok Dance Challenge: Content Creativity and Character Value for Elementary School Students - Ratri, Dyan Permata; Muhroji, Muhroji; Prayitno, Harun Joko; Adhantoro, Muhammad Syahriandi; Putra, Chandra Anugrah (Buletin KKN Pendidikan, 2024)
This study aims to describe the role of parents in supervising children's use of cellphones, the factors that cause children to like dance challenge content and the impact of using the tiktok application on children's character. This type of qualitative research uses observation, interview, and documentation data collection techniques. Data sources were obtained from parents, class teachers, principals, students. The results showed that dance challenge content has positive and negative impacts on the character of elementary school children. The positive impact of children who like tiktok dance challenges is creative and able to keep up with the development of science and technology. The negative impact shows a lack of religious character values, discipline, and national spirit. Based on this data, it can be concluded that there is an impact of tiktok dance challenge content on children's character.